DEEP LEARNING AS A PATHWAY TO PEDAGOGICAL TRANSFORMATION IN INDONESIA - Ambarita, Jenri; Purnamasari, Uci; Siahaya, Agusthina (Jurnal Penelitian Kebijakan Pendidikan, 2025)
This study examines the implementation of deep learning in Indonesia’s education system and evaluates its effectiveness in fostering students’ critical thinking, problem-solving, creativity, and selfreflection. The central argument highlights the need for a pedagogical shift from rote memorization to understanding and application to achieve meaningful educational outcomes. Using a qualitative literature review and thematic analysis, the study identifies patterns, impacts, and challenges specific to Indonesia. Findings reveal that although deep learning strategies are emerging, traditional methods prevail. Key factors for successful implementation include institutional readiness, teacher training, and supportive policies. Major barriers are limited teacher competence, insufficient technological infrastructure, and assessments that emphasize memorization. The study concludes that integrating mindful, meaningful, and joyful learning is crucial for student engagement. Policy reforms, improved technological access, and strengthened teacher professional development are recommended to establish innovative, student-centered learning environments that enhance education quality in Indonesia.